Examining the different patterns of personal finance management between married and bachelor groups - Sharban,, Ramkumar. (Universiti Malaysia Sarawak, (UNIMAS), 2009)
Personal finance is the application of the principles of finance to the monetary decisions of an individual or family unit. Managing personal finance is important to achieving the monetary goals. Hence, this research is important to find out the underlying determine how subjects perceive personal finance by different based of demographic (marital status) and different stages of personal income. This study is to examine the personal spending of the different types of people which is categories as married and bachelors. The study is basically looking at the issues of personal finance management among Malaysian peoples in Kuching City, Sarawak. Questionnaires were distributed and analyzed through frequency distribution, the Mean, MANOVA, One Way ANOVA, and as well as T-test analysis; had been used to identify the interrelations and significant differences between tendency of personal finance and married and bachelor groups. The result shows that there is a significant difference between dependent variables and marital status. There are five dependent variable factors were found to be a reason for managing personal finance. They are money management factor, Entertainment, Saving and Investment, Liabilities and Retirement.